Pengaruh Tax Avoidance dan Struktur Modal Terhadap Nilai Perusahaan dengan Kualitas Audit Sebagai Variabel Moderasi - Marliana, Avilla; Norsita, Mega (Jurnal IAKP : Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2025)
This study aims to examine the effect of tax avoidance and capital structure on firm value with audit quality as a moderating variable (empirical study of manufacturing companies listed on the Indonesia Stock Exchange). This type of research is quantitative research using secondary data. The sample determination used the purposive sampling method and obtained 80 data from consumer goods sector manufacturing companies listed on the Indonesia Stock Exchange in 2019-2022. The results of this study indicate that tax avoidance and capital structure have a negative effect on firm value, and audit quality as a moderating variable does not affect the relationship between tax avoidance and firm value.